LITERASI DIGITAL MAHASISWA VOKASI DI ERA PANDEMI COVID-19 - Endang Fitriyah Mannan; Muhammad Rifky Nurpratama (Info Bibliotheca: Jurnal Perpustakaan dan Ilmu Informasi, 2022)
Digital technology is developing very rapidly and touching all sectors of life, including the world of education. Efforts to improve the digital skills of the community, especially the younger generation, have begun to minimize negative content that has flooded the digital space. The Covid-19 pandemic The COVID-19 pandemic has accelerated digital transformation in Indonesia. This study aims to describe and measure the level of digital literacy among vocational students in the pandemic era. The research method used is descriptive quantitative. The object that became the research target were all active students of the Vocational Faculty, Airlangga University. The sampling method in this study used purposive random sampling. Data collection in this study used a survey method through the distribution of questionnaires. The data extracted to determine the level of digital literacy of students includes technology, ethics and cognitive. The data obtained were then analyzed using SPSS version 25. The results showed that students' digital literacy skills were in the high category. Regarding the online learning format for vocational education, research findings mention the need for digital literacy education for students. The results of the research can be used as recommendations to improve the quality of vocational education with online/online formats and materials for making digital literacy education modules for students.